EFFECTIVENESS OF GLOBAL MANAGEMENT METHODS IN HEALTHCARE SYSTEMS - Umarova Gulbahor Mahmudjonovna (Western European Studies, 2025)
This article analyzes the role and importance of global management approaches in improving efficiency in healthcare systems. Management models such as Total Quality Management, Lean Management, Performance Management, Strategic Planning are considered on a theoretical basis, and management methods in the healthcare system of Uzbekistan are analyzed in comparison with international experience. Linguistic competence, in particular the role of English in healthcare management, is also highlighted. The article shows the differences in the management strategies of the healthcare systems of advanced countries - the USA, Great Britain, Germany, South Korea, and gives practical suggestions for Uzbekistan.
Keywords: Global management; healthcare system; TQM; Lean Management